THE EFFECTIVENESS OF IMPLEMENTING DISTANCE LEARNING FOR ISLAMIC BOARDING HOUSE STUDENTS - Ngurah Pandji Mertha Agung Durya; Siti Aniqoh Shofwani; Ira Nurmala; Dwi Novaria Misidawati; Ahmad Hariyadi (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2023)
Since 2020 all educational institutions have implemented distance learning. Distance learning is implemented in order to inhibit the spread of the Covid-19 virus so that it does not spread more widely. The purpose of this research is find out the effectiveness of distance learning implementation at the Al Badrul Falah Islamic Boarding School. This study used qualitative research with the snowball method. Data collection techniques used interviews with teachers and students. The results of this study indicate that distance learning is effective to be carried out using e-learning media and social media. In addition, the application of effective distance learning is a solution for continuity of learning when face-to-face learning cannot be held.